VIDEODANCE EXPERIMENTS: THE INFLUENCE OF THE AUDIOVISUAL ON THE VISUALITY OF DANCE - Lopes Guedes, Anibal (2022)
The paper aims to develop experiments in videodance. Videodance is constituted from a field of intersection between dance and audiovisual. Thus, the study aims to conceive, create and produce three videodances from the same choreography, having Spanghero (2003) as main reference. The research is exploratory in nature and involves a research in art, as the videodances were produced by the researchers and informs our discussion. As results we can point out: the audiovisual influences the visuality of the dance; the creation processes of the choreographer and of the filmmaker are different; the audiovisual resources provide new perspectives on the visuality of dance.